Effect of fly ash on the potential alkali silica reaction of ferronickel slag aggregate - Saha, Ashish Kumer; Sarker, Prabir (2017)
Ferronickel slag (FNS) is generated as a by-product during the production of ferronickel. The rapid cooling process of the slag may lead to the formation of amorphous silica. Therefore, partial replacement of sand with nickel slag aggregate has potential to show expansion due to alkali silica reaction (ASR). The present study evaluates the effect of fly ash as a supplementary cementing material (SCM) to mitigate this deleterious expansion. Fly ash was used as 10%, 20% and 30% of the binder in order to investigate its effect on the reduction of ASR. The results of accelerated mortar bar test (AMBT) show that 10% replacement of cement by fly ash was unable to reduce expansion below the required level. Furthermore, use of 20% fly ash reduced the expansion by 45% compared to 10% fly ash samples, but still the expansion level of the samples was within the category of slowly reactive aggregate according to AS 1141.60.1-14. However, use of 30% fly ash reduced ASR expansion below the 10-day and 21-day limits of the standard. It was found that expansion did not increase for the extended period of test in the samples containing 30% fly ash. The microstructural observation was carried out to confirm the effectiveness of fly ash to mitigate this expansion.